A Study of Chinese Translation of The Cambridge Grammar of the English Language from the Perspective of Grammatical Metaphor - Qiao, Yizhuo (Pacific International Journal, 2024)
In Systemic Functional Linguistics, grammatical metaphor is categorized into ideational and interpersonal types. Translation, as a process of code-switching, involves choosing between congruent and metaphorical forms, each serving different communicative purposes. Distinguishing these forms clarifies their distinct functions. This paper explores the use and importance of grammatical metaphors in translating The Cambridge Grammar of the English Language based on the author’s independent translation practice. Given this, the study achieves three objectives through quantitative and qualitative analysis: (1) examining the distribution of grammatical metaphors in the translation of The Cambridge Grammar of the English Language; (2) exploring the reasons behind their emergence; and (3) analyzing the role these metaphors play in the translation. Translation strategies were classified into two types based on the retention of grammatical metaphors: congruent translation, which simplifies the text and reduces metaphors, and metaphorical translation, which sustains a formal, academic, and concise style. The study reveals that the same translation techniques can be applied across various word, sentence, and text types, with different contexts requiring different methods even for identical grammatical and semantic units. Regardless of whether metaphors are retained, it is essential to ensure faithfulness, fluency, and aesthetics of the translation. Translators should avoid rigid application and decide on metaphor preservation based on the specific context and text type to best convey the original meaning.